Effectiveness of vesicular arbuscular mycorrhiza on root development of sago palm plantlets / Siti Sahmsiah Sahmat - Sahmat, Siti Sahmsiah (2014)
The state of Sarawak in Malaysia started the world’s first plantation of sago palm (Metroxylon sagu Rottboll) in Mukah Division in the 1990s to cope with the growing demands of sago flour. Sago palm planting material using tissue culture propagation has been hindered by the slow nursery growth of the plantlets. Earlier studies have shown that the introduction of indigenous mycorrhiza belonging to the Glomus species isolated from wild sago palm have accelerated growth of tissue cultured plantlets in the nursery stage. Arum type with intercellular hyphae of arbuscles was discovered in the study. The successful isolation and bulking of the vesicular arbuscular mycorrhiza (VAM) inoculum using the alternate host, Allium sp. enabled study on the growth response of sago plantlets to VAM which indicated that the symbiosis relationship overcoming transplanting shock and accelerating nursery establishment. The introduction of VAM to in-vitro sago palm plantlet has not been investigated. Therefore, the main objective is to study the effectiveness of VAM on root development of sago palm plantlets. Inoculums obtained from the wild sago palms, confirmed as VAM were produced in a cultured media. A range of pH 3.8 to pH 6 was prepared to observe the highest number of spore production. The infectivity of cultured spores was determined by the colonization of VAM on alternate host and confirmed by the presence of VAM characteristic. The cultured spore was inoculated to the plantlets aged from stage three aged from zero to eight month. The result showed the highest production of spores occurred at pH 4.2 after 21 days of inoculation to the host plant of Allium sp. The cultured spores colonized the roots of the Allium sp. indicating its infectivity and therefore were used as a source of inoculum to infect the tissue plantlets of sago palm. An experiment based on complete randomized block design (CRDB) technique was carried out in the biotechnology laboratory of CRAUN Research Sdn. Bhd. to determine the plantlet infections after being surface sterilized with Teepol detergent. The spore number that resulted in the most successful infection of sago palm plantlets was 15 spores with 10.6% infection on plantlets aging between zero to two months old. The beneficial effect of VAM spores inoculated micropropagated plantlets at the in-vitro stage was reflected by the early initiation of lateral root growth. Thus, with accelerated root establishment in the in-vitro stage will overcome the problem of using micropropagated plantlets as planting materials.